2009
DOI: 10.1016/j.vaccine.2009.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Telemetric analysis to detect febrile responses in mice following vaccination with a live-attenuated virus vaccine

Abstract: Nonhuman primates (NHP) are considered to be the most appropriate model for predicting how humans will respond to many infectious diseases. Due to ethical and monetary concerns associated with the use of NHP, rodent models that are as predictive of responses likely to be seen in human vaccine recipients are warranted. Using implanted telemetry devices, body temperature and activity were monitored in inbred and outbred mouse strains following administration of the live-attenuated vaccine for Venezuelan equine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Live attenuated V3526 has shown excellent protective efficacy in animal models [17,18] and robust immune response in phase I clinical trial [25]. However, its development as a live attenuated vaccine was halted due to a flu-like syndrome and fever in the recipients [24,25]. Therefore, it will be desirable to inactivate V3526 in a way that conserves its immunogenicity to generate a safer vaccine candidate without any residual virulence.…”
Section: Group(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Live attenuated V3526 has shown excellent protective efficacy in animal models [17,18] and robust immune response in phase I clinical trial [25]. However, its development as a live attenuated vaccine was halted due to a flu-like syndrome and fever in the recipients [24,25]. Therefore, it will be desirable to inactivate V3526 in a way that conserves its immunogenicity to generate a safer vaccine candidate without any residual virulence.…”
Section: Group(s)mentioning
confidence: 99%
“…V3526 has excellent immunogenic activity, but also causes febrile illness and low level neurotropism in non human primates [17,18,[21][22][23]. In phase I clinical trial, V3526 induced a robust immune response; however, a high frequency of fever and a flu-like syndrome were reported which led to the cessation of the development of V3526 as a live attenuated vaccine [24,25].The residual virulence associated with the vaccine candidates has again focused the attention on the inactivated vaccine preparation. We have previously demonstrated that 1,5 iodonaphthyl azide (INA) completely inactivated the virulent strain of VEEV, V3000 in vitro [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, evaluation of the V3526 vaccine in Phase 1 clinical studies (Holley et al, 2008) resulted in adverse events in a number of vaccine recipients that stopped further development of the vaccine as a live attenuated vaccine product. Because live attenuated vaccines for VEEV have shown high frequency of adverse reactions (Kinney 1972; Edelman et al, 1979; Martin et al, 2009), DVC sought to produce a non-infectious V3526 vaccine, the intent of which was to significantly reduce the adverse reaction profile of V3526, while retaining its potential as a protective immunogen against subtype I VEEV. Of particular interest was to proceed with the development of an inactivated V3526 that ultimately could be used as a primary vaccine to protect personnel at risk to accidental or intentional VEEV exposure.…”
Section: 0 Introductionmentioning
confidence: 99%
“…DNA vaccines, administered by several means, have also shown efficacy in rodents and nonhuman primates (12)(13)(14). Live attenuated vaccines developed using modern molecular techniques provided good immunogenicity, safety, and protection in rodents and nonhuman primates although in phase I clinical trials mild fever responses were seen at very low dosages (15)(16)(17). Other approaches using live attenuated vaccines are being evaluated and have shown promise in mice and nonhuman primates (18)(19)(20).…”
mentioning
confidence: 99%